Application of a non-invasive form-finding algorithm to the ring compression test with varying friction coefficients - Landkammer, Philipp; Steinmann, Paul (Key Engineering Materials, 2015)
It is a great challenge in the development of functional components to determine the optimal blank design (material configuration) of a workpiece according to a specific forming process, while knowing the desired target geometry (spatial configuration). A new iterative non-invasive algorithm, which is purely based on geometrical considerations, is developed to solve inverse form finding problems. The update-step is performed by mapping the nodal spatial difference vector, between the computed spatial coordinates and the desired spatial target coordinates, with a smoothed deformation gradient to the discretized material configuration. The iterative optimization approach can be easily coupled non-invasively via subroutines to arbitrary finite element codes such that the pre-processing, the solving and the post-processing can be performed by the habitual simulation software. This is exemplary demonstrated by an interacting between Matlab (update procedure) and MSC. MarcMentat (forming simulation). The algorithm succeeds for a parameter study of a ring compression test within nearly linear convergence rates, despite highly deformed elements and tangential contact with varying friction parameter
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-TM.applic_3
Keywords: Friction; Inverse form finding; Plasticity; Tangential contact